The Massive Bleeding after the Operation of Hip Joint Surgery with the Acquired Haemorrhagic Coagulation Factor XIII(13) Deficiency: Two Case Reports. (28th February 2013) - Kanda, Akio; Kaneko, Kazuo; Obayashi, Osamu; Mogami, Atsuhiko
Abstract : Two women, aged 81 and 61, became haemorrhagic after surgery. Their previous surgeries were uneventful with no unexpected bleeding observed. Blood tests prior to the current surgeries indicated normal values including those related to coagulation. There were no problems with the current surgeries prior to leaving the operating room. At 3 hours after the surgery, the 81-year-old patient had an outflow of the drain at 1290 grams and her blood pressure decreased. She had disseminated intravascular coagulation (DIC). The 61-year-old woman had repeated haemorrhages after her current surgery for a long time. Their abnormal haemorrhages were caused by a deficiency of coagulation factor XIII(13). The mechanism of haemorrhagic coagulation factor XIII(13) deficiency is not understood, and it is a rare disorder. The only diagnostic method to detect this disorder is to measure factor XIII(13) activity in the blood. In this paper, we used Arabic and Roman numerals at the same time to avoid confusion of coagulation factor XIII(13) with coagulation factor VIII(8) that causes hemophilia A.